Suitability of Pueraria phaseoloides, Chromoleana odorata and Tithonia diversifolia for nematode management in Musa cropping systems - Schosser, B.; Hauser, S.; Sikora, R.A. (2006)
Mulching with plant organic matter has been shown to reduce nematode population densities in various cropping systems. The level of nematode control is increased when such mulches are incorporated into the soil as organic amendments. Chromolaena odorata, Tithonia diversifolia and Pueraria phaseoloides are common cover crops in West and Central Africa that produce large quantities of nutrient rich biomass. The aim of this study was to determine, if in-situ mulching of C. odorata, T. diversifolia and P. phaseoloides is suitable for nematode control in Musa production. In a pot trial, the susceptibility of these plants to spiral nematodes was investigated. The effects of different quantities of surface mulch on nematode population densities in the soil and in banana roots also were determined. All mulch types and all quantities led to a reduction in nematode population densities in the soil. The strongest nematode reductions were observed in the Pueraria treatments. In treatments containing banana plants mulching improved plant growth compared to the clean-fallowed soil and induced lower root infestation rates. However, nematode soil populations were higher in mulched than in non-mulched banana treatments. Plant parasitic nematodes also were isolated from roots of all three cover crop species and all three plants caused an increase in nematode numbers in the soil. Therefore, the tested cover crops proved unsuitable for nematode control in a system with the highly susceptible bananas. Further examinations are needed to determine whether or not the positive effects of surface mulching on plantain plant growth and root infestation rates also have positive effects on yield in an in-situ mulching system in the presence of nematodes.